Facebook’s wealth and its role in supporting gender identity and sexual orientation: an ethnographic study - محمد أبو الحسن منال (International Journal of Social Communication, 2019)
This research aimed to explore the extent to which Facebook supports gender identity and sexual orientation. The term "gender" was used within its international context, both in terms of its definition and its application on a global scale, given its multiple definitions and varying interpretations across Western and Arab contexts. The research also relied on media richness theory, considering the platform's role in enriching the media process. A virtual ethnographic approach was employed to access information sources that are difficult to obtain through descriptive research or direct interaction. The research instrument consisted of online interviews with female members of four Arab lesbian groups on Facebook. A semi-structured interview tool was used, comprising ten personal questions that allowed participants to speak freely about their gender identity and sexual orientation. The sample included participants from four nationalities (Egyptian, Saudi, Kuwaiti, and Algerian), and the study was conducted over three months (September, October, and November 2018). The study reached several conclusions that confirm the premises of the media richness theory, the epistemological premises of the research, and previous studies. Among the most important of these is the ability of Facebook to be a supporter and media alternative for Arab lesbians due to its ease of use, the information available in Facebook groups, and the real social, security, and religious conditions, along with a general weakness in the participants' knowledge of international trends in supporting gender identity and sexual orientations, and with a steady increase in the number of participants within the groups in the research sample. It also showed the ability of the participants to communicate their ideas via Facebook, despite the risk and lack of credibility.